Assessing Symptom Accommodation of Social Anxiety Symptoms Among Chinese Adults: Factor Structure and Psychometric Properties of Family Accommodation Scale Anxiety—Adult Report - Lou, Congmei; Zhou, Xiaolu; Lebowitz, Eli R.; Williams, Laurel L.; Storch, Eric A. (Frontiers in Psychology, 2020)
Objective: Symptom accommodation has been found to be an important interpersonal construct associated with more severe symptoms, lower levels of functioning, and worse treatment outcomes across various mental health conditions, including social anxiety. However, research on this phenomenon is surprisingly absent in Chinese culture where interpersonal relationships are highly emphasized. This may be due to the absence of a valid Chinese symptom accommodation measure for individuals with social anxiety symptoms. The current study aimed to examine the factor structure and psychometric properties of the Family Accommodation Scale Anxiety – Adult Report (FASA-AR) in a Chinese adult sample. Methods: 375 Chinese undergraduate students with social anxiety symptoms completed a battery of self-report measures assessing symptom accommodation in relation to social anxiety symptoms and related impairments, as well as overall symptoms of anxiety and depression. Results: Confirmatory factor analysis supported a two-factor model of symptom accommodation, with factors named Participation in symptom-related behaviors, and Modification of functioning. The internal consistencies for the FASA-AR total score and subscale scores were good. Convergent validity was evidenced by significant positive association with ratings of social anxiety symptoms, social anxiety related impairments, and anxiety symptoms. Divergent validity was supported by non-significant relation with depression symptoms. Nearly all participants (94.7%) endorsed at least some level of accommodating in the past month. There were no gender differences on the FASA-AR total score; however, females scored higher on the Participation in symptom-related behaviors subscale. Conclusions: Symptom accommodation is an important construct and is related to social anxiety symptoms. The FASA-AR demonstrated a clear two-factor latent structure, and possessed good psychometric properties that can validly and reliably assess symptom accommodation of social anxiety among Chinese adults.